From incision to outcomes: a comparative dive into the functional outcomes of arthroscopic all-inside and outside in meniscal repair techniques - Malhotra, Ashu; Srivastav, Shekhar; Singh, Harjoban; Sen, Biswarup (International Journal of Research in Orthopaedics, 2024)
Background: Meniscal repair has been associated with superior outcomes, including enhanced knee function, increased activity levels, reduced osteoarthritis progression, cost savings, and improved long-term functional outcome scores compared to partial meniscectomy. This study aimed to evaluate and compare the functional outcomes of meniscal repairs performed using the outside-in and all-inside techniques, utilizing the International Knee Documentation Committee (IKDC), Tegner Lysholm (TL) scores and comparing our results with previous studies. Methods: This prospective study included 53 patients with traumatic meniscal tears and associated ligamentous injuries that underwent arthroscopic meniscal repair. Details of investigations were recorded, and knee functional assessment was performed using the 2000 IKDC score and TL scores. Results: The mean age of the patients was 28±8.41 years, with 41 (77.36%) males and 12 (22.64%) females. At the final follow-up of 1 year, the IKDC scores in the all-inside group and outside in group were 93.26±4.45 and 94.31±2.63. The TL scores in the all-inside and outside in groups were 95.33±2.45 and 96±1.00. No statistically significant difference was noted between the two groups (p value >0.005). Conclusions: Meniscal repairs in the two groups in our series demonstrated favourable clinical outcomes, as evidenced by significant improvements in IKDC score with averages increasing from 25.31 to 93.26 and from 25.91 to 94.31 in all-inside and outside-in groups respectively. The TL sores showed an improvement from 21.07 to 95.33 and from22.43 to 96.00 in all-inside and outside-in groups respectively. In conclusion, short-term results of traumatic meniscal tears with repair are promising, leading to significant improvements in knee function irrespective of concomitant injuries and the type of repair.